Patterns of Implicit Structures in the Amari Discours - Alketbi , Mariam; Alabidi , Leila (Al-Adab Journal, 2026)
This research explores the implicit structures (ansaq) in the speeches and letters of Umar ibn al-Khattab from religious, social, and political perspectives. It examines how these structures guided the Islamic society, fostering values of justice, equality, and unity. The study highlights the principles embedded in Umar’s discourse that contributed to building the Islamic state, such as the purity of faith, social solidarity, and good governance. Additionally, the research emphasizes the role of political frameworks in organizing state affairs through the establishment of administrative bureaus (diwans) and the unification of the Hijri calendar. The study concludes by stressing the importance of analyzing implicit structures in Islamic discourses to understand historical and social dynamics, recommending the application of cultural criticism to other texts in Islamic heritage to uncover their hidden values and their role in shaping society.